1975
DOI: 10.1083/jcb.65.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteins synthesized by rabbit reticulocytes.

Abstract: Intact rabbit reticulocyte cells synthesize two predominant species of polypeptides which are components of the cell plasma membrane. Previous work (Lodish, H. F. 1973. Proc. Natl. Acad. Sci. U. S. A. 70:1526-1530 showed that these proteins were synthesized by polyribosomes not attached to membranes. We show here that both polypeptides are confined to the cytoplasmic surface of the cell membrane. These studies utilized iodination of whole cells and of membranes with lactoperoxidase, and digestion of whole cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…Biosynthetic studies with rabbit reticulocytes have shown that two nonglobin proteins of 33,000 and 56,000 daltons (8) are made by the free polyribosomes in the cytoplasm and then attach to the inner surface of the membrane (9). The latter protein loses about 30 amino acids with incorporation into the membrane.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Biosynthetic studies with rabbit reticulocytes have shown that two nonglobin proteins of 33,000 and 56,000 daltons (8) are made by the free polyribosomes in the cytoplasm and then attach to the inner surface of the membrane (9). The latter protein loses about 30 amino acids with incorporation into the membrane.…”
mentioning
confidence: 99%
“…Red cells that had reached a "steady state" of radioactive labeling about 10 days after the injection of isotope were treated with a-chymotrypsin to digest the proteins on their external surface (9 Autoradiofluorography. In order to enhance the detection of 35S in each band, we permeated the gels with a scintillant, 20% (wt/vol) 2,5-diphenyloxazole (PPO, Interex, Natick, Mass.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that several proteins, now known to be cytoskeletal proteins, are made on membrane-free polysomes (15,16). One of my favorite experiments demonstrated that the major red cell membrane and cytoskeleton proteins are made at different times during development (17).…”
Section: Biogenesis Of Membrane Proteins: the 1970smentioning
confidence: 99%
“…Sci. USA 84 (1987) 6233 face of the plasma membrane (27)(28)(29)(30)(31). The best-characterized protein is pp60vsrc, the transforming protein of Rous sarcoma virus that is modified by the covalent attachment of the 14-carbon saturated fatty acid myristic acid to its NH2 terminus following translation on free polysomes and is then transported within 15 min to the plasma membrane (32,33).…”
mentioning
confidence: 99%